DAMPAK IMPLEMENTASI TRANSAKSI NON TUNAI PEMERINTAH DAERAH TERHADAP KARAKTERISTIK MASYARAKAT DI KABUPATEN KEEROM - Wa Ariadi; Ahadi Rerung; Windy Jatmika (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to determine the impact of the implementation of non-cash transactions with measuring variables are government commitment, human resource readiness, and cooperation on community characteristics. The study used a sample of 75 people from all Work Units or offices in the Keerom District government related to finance. The results indicate that partially the implementation of non-Cash transactions with the variable commitment of the local government (X1), Readiness of Human Resources (X2), and Cooperation (X3) have an impact on the Characteristics of the Community (Y) in Keerom Regency which can be seen from the test value t-count compared to t-table as well as a significant level. Implementation of non-cash transactions jointly or simultaneously has an impact on the characteristics of the community (Y) in Keerom Regency which is done by comparing p_value or probability (F-statistics) with a significant level. From the calculation of the magnitude of the probability (F-statistic) and the significant level is set at a = 5% = 0.05, so the p_value or probability of this result then the comparison (f-count) with the value of 17,822 with a significant level is 0,000. These results explain that simultaneous implementation of non-cash transactions with government commitment variable (X1), human resource readiness variable (X2), cooperation variable (X3) together have an impact on community characteristics (Y), so the hypothesis stating that the variables of government commitment, readiness of human resources, and cooperation have a positive and significant effect on the characteristics of the community declared acceptable and can be verified. Keywords: Government Commitment, Human Resources, Cooperation and Community Characteristics.